RC42's:Improved data security technique in wireless local network (2010)
This paper exposes the weakness of RC4 encryption; a data protection algorithm used by wired equivalent privacy of WLAN. It shows that inspite of general acclaim invulnerability of Wired Equivalent Privacy WEP used in WLAN there are still several loop holes that computer harkers can use to circumvent through our wireless networks. These vulnerabilities create the potential for active and passive attacks which could allow attackers to decrypt or inject data in a network. To buttress the extent of the vulnerability of RC4 used by WEP, Stuart J. Kerry, the chairman for the IEEE 802.11 standard groups, pointed out that WEP has shortcomings and promised to address all the weakness of WEP. This paper proffers an improved method called RC4-2's algorithm, which makes it difficult for harkers to delete the key and cipher text of RC4, whenever there is collision. The RC4-2 encrypts by exclusively Oring the message with the key and 2's complement of the result will then become the encrypted message. Therefore, this paper is not only an eye opener to the vulnerability of WEP in WLAN but provides a perfect improvement on RC4 which takes care of RC4 weaknesses.